Cocoa flavanol effects on markers of oxidative stress and recovery after muscle damage protocol in elite rugby players - Carvalho, Flavia Giolo de [UNESP]; Fisher, Mitchell Garant; Thornley, Todd T.; Roemer, Karen; Pritchett, Robert; Freitas, Ellen Cristini de [UNESP]; Pritchett, Kelly (Elsevier B.V., 2019)
Objectives: Strenuous exercise can impair athletic performance due to muscular inflammation and oxidative stress. Antioxidants such as cocoa flavanols have been used as a supplement to prevent oxidative stress; however, the benefits of dietary antioxidants for athletic performance after muscle soreness (MS) is unclear. The purpose of this study was to examine the effects of cocoa flavanols after a MS inducing protocol. Methods: In a randomized, double-blinded design, 13 male collegiate rugby players consumed either chocolate milk (CHOC) or chocolate milk with additional cocoa flavanols (CocoaCHOC) during a 7-d loading phase. MS was induced by a drop jump protocol on day 5 of the intervention. Athlete performance was assessed with vertical-jump and yo-yo tests and subjective measures of soreness 5 d before and 2 d post-MS protocol. Urinary markers of oxidative stress (isoprostanes) were assessed before and 48 h post-MS. Results: No changes were observed between the groups over time for isometric torque (P=.63), vertical jump performance (P=.39), and yo-yo testing (P =.57) between the trials. No interaction was found in isoprostanes levels between the trials (CocoaCHOC baseline: 88 +/- 0.38 pg/mL and 48 h post-MS: 81 +/- 0.53 pg/mL; P=.82; and CHOC baseline: 98 +/- 0.96 pg/mL and 48 h post-MS: 96 +/- 0.38 pg/mL; P=.59). No main effect (treatment x time; P = .58) was observed for isoprostanes. Although not significant, the CocoaCHOC group ran 97 meters further than the CHOC group in the yo-yo test. Conclusions: Cocoa flavanols added to a post-exercise recovery beverage for 7 d has no oxidative stress or athletic performance benefits. (C) 2018 Published by Elsevier Inc.
Keywords: Rugby; chocolate milk; cocoa flavanols; muscle damage; recovery